United by Recession, Disillusioned by Rescission: The Political Economy of a Detribalised Financial Networking Scheme (MMM) in Nigeria - Omilusi, Mike; Ojogbede, Olamide Temitayo; Adeoye, Michael Ade (African Journal of Stability and Development (AJSD), 2018)
There is no disputing the fact that Nigeria is a heterogeneous society, comprising peoples of different ethnic, linguistic and cultural backgrounds. Interestingly, the cords that bind most Nigerians, in spite of these cleavages, have been some seemingly ‘insignificant’ ideas, concepts and issues like their unmatched passion for football. Apart from the social import/impact of the love for football, the economic situation in the country seems to have brought on them a common fate and an uncommon unity. Until recently, Africa’s biggest economy, Nigeria was in a recession, being its first in 20 years. Unfortunately, hyperinflation experienced in the past few years also increased the spate of the ugly trend. It is against this backdrop that the MMM Ponzi scheme made a grand and triumphant entrance into the Nigerian investment market in 2016. Obviously, quite a lot has been written concerning the MMM speculative scheme which eroded the Nigerian financial space. Both the conventional and the social media were awash with the various foreseeable gains and pains associated with the scheme to the individual investors. In a departure from this narrative, this essay focuses on the social integration value, the scheme engendered in the Nigerian society through its networking. The methodology employed consists of desk research including, inter alia, analysing books, journal articles and newspaper articles. In addition, websites from several local and international organisations relevant to the study were also utilised